Computer modeling of the stress-strain state of vibrating machine frames with spatial vibrations - Nesterenko, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article analyzes the stress-strain state of vibrating platforms with vertical and horizontal vibration exciters. The stiffness of the frames under the action of both vertical and horizontal loads is considered. Deflections in elements of the metal frame were calculated. The type of stress distribution in frame elements was studied. Places of stress concentration are determined for these structures of vibration platform the metal frame. The values of these stresses are much smaller than the calculated resistance of steel, which makes it possible to optimize the frame design by reducing its metal capacity. The metal capacity of the frame can be reduced by changing the thickness of the frame elements by 20%.
Keywords: stress-strain state; vibrating platforms; vibration exciter; spatial vibrations; computer simulation